DETERMINING THE SEQUESTRATION POTENTIAL OF HOME-GROWN VEGETATION WITHIN AN URBAN RESIDENTIAL PLOT. - Bose, Sumit; Roy, Madhumita (International Journal of Research -GRANTHAALAYAH, 2025)
Urban Households – the buildings with their inhabitants are one of the major sources of carbon emission leading to climate change. There is an urgent need to mitigate this problem. Initiatives generally followed are restricting energy use and reducing energy-intensive activities and materials. However, the best way of mitigating CO2 emitted by the building, is to sequester it through plants grown inside the premises. This paper intends to study the scope of sequestration of CO2 by plantation grown within the plot of a multi-storied and multi-tenement residential buildings in the urban area of Newtown, beside Kolkata, in India, in comparison to quantity of CO2 emitted from the operation phase of the building’s life-cycle. The aim of the study is to find how much of the CO2 emitted by the building can be sequestered by growing plants inside the same plot of the building. CO2 emission is quantified from activities like – electricity usage, fuel (LPG) for cooking, fuel (Petrol) usage for vehicle idling time inside the building premises, respiration and potable water production and the total emission is compared to scope of sequestration by plantation inside the plot. Quantitative analysis of CO2 emitted by a multi-tenement multi-storied residential building and CO2 sequestered by plantation grown within the premises show that plantation in only 4% of the plot area, as per stipulation by local municipal authority, can sequester only 4% of the CO2 emitted by the building. However, assuming a scenario with increased plantation, which is practical and achievable, this proportion of sequestration can be increased to as high as 40%.